2011
DOI: 10.1007/s11060-011-0550-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vitro and in vivo approaches to studying brain colonization by breast cancer cells

Abstract: Brain metastases occur in 20 to 40% of patients with metastatic breast cancer. The process is complex and depends on successful cancer cell evasion from the primary tumor, distribution and survival within the blood stream and cerebral microvasculature, penetration of the blood brain barrier and proliferation within the brain microenvironment. The initial steps of brain colonization are difficult to study in vivo. Therefore, in vitro assays have been developed to mimic this process. Most commonly, in vitro stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…However, as described previously, 12 large pores may allow ECs to migrate and grow on the lower face of the inserts. Hence, the presence of a multilayered endothelium means that the final cellular structure is no longer representative of the monolayer situation in vivo.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…However, as described previously, 12 large pores may allow ECs to migrate and grow on the lower face of the inserts. Hence, the presence of a multilayered endothelium means that the final cellular structure is no longer representative of the monolayer situation in vivo.…”
mentioning
confidence: 76%
“…24,25 Unfortunately, when this original model was transposed to 3-μm-pore inserts, the ECs crossed the porous membrane to form a second layer on the lower face. 12 In vivo, circulating prometastatic cancer cells pass through a single layer of ECs when they transmigrate through brain microvessels. Hence, the migration of ECs through 3-μm-pore inserts prevents the model from being used to investigate this process in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…There may be different mechanisms involved in CNS metastasis from non-CNS metastatic sites. Previous studies have demonstrated that metastatic extravasation into the brain takes significantly longer than it does in other organs [44]. In solid tumors, the adhesion of circulating tumor cells (CTCs) to the vascular endothelium becomes a crucial starting point of metastasis that precedes the invasion and extravasation of CTCs, and the formation of micrometastasis foci.…”
Section: Discussionmentioning
confidence: 99%
“…The survival of arrested cancer cells within brain capillaries may be a rate-limiting step in metastatic progression, since cancer cell penetration of the vessel wall in the brain is much slower than in progression and impacts the success of tumor cells to survive and grow within the brain [3537]. …”
Section: Discussionmentioning
confidence: 99%